Near-Infrared Photoimmunotherapy in Brain Tumors—An Unexplored Frontier - Haruka Yamaguchi; Masayasu Okada; Takuya Otani; Jotaro On; Satoshi Shibuma; Toru Takino; Jun Watanabe; Yoshihiro Tsukamoto; Ryosuke Ogura; Makoto Oishi; Takamasa Suzuki; Akihiro Ishikawa; et al. (Pharmaceuticals)
Near-infrared photoimmunotherapy (NIR-PIT) is a promising cancer treatment that uses near-infrared light to activate a conjugate of a monoclonal antibody (mAb) and a photoactivatable silica phthalocyanine dye (IRDye700DX: IR700). Unlike conventional photodynamic therapy (PDT), NIR-PIT selectively destroys targeted tumor cells while preserving the surrounding normal tissue and providing superior tissue penetration. Recently, NIR-PIT has been approved for the treatment of unresectable recurrent head and neck cancers in Japan. It induces highly selective cancer cell death; therefore, it is expected to be a new curative treatment option for various cancers, including brain tumors. In this review, we compare the principles of NIR-PIT and PDT and discuss the potential applications of NIR-PIT for brain tumors. We selected targetable proteins across various types of brain tumors and devised a strategy to effectively pass the mAb–IR700 conjugate through the blood–brain barrier (BBB), which is a significant challenge for NIR-PIT in treating brain tumors. Innovative approaches for delivering the mAb–IR700 conjugate across the BBB include exosomes, nanoparticle-based systems, and cell-penetrating peptides. Small-molecule compounds, such as affibodies, are anticipated to rapidly accumulate in tumors within intracranial models, and our preliminary experiments demonstrated rapid uptake. NIR-PIT also induces immunogenic cell death and activates the anti-tumor immune response. Overall, NIR-PIT is a promising approach for treating brain tumors. It has the potential to overcome the limitations of conventional therapies and offers new hope to patients with brain tumors.